Integration, Agglomeration and Welfare - Michael Pflüger; Jens Südekum (Institute for the Study of Labor (IZA), 2004)
This paper studies the social desirability of agglomeration and the efficiency arguments for policy intervention in a simple, analytically solvable ?new economic geography? model with two trade integrating regions. The location pattern emerging as market equilibrium is ?bubbleshaped?, i.e. it features dispersion of firms both at high and low trade costs and stable equilibria with partial agglomeration of firms in addition to core-periphery equilibria for intermediate levels of trade costs. Our central finding is that the market equilibrium is characterised by over-agglomeration for high trade costs and under-agglomeration for low trade costs. For very high and very low levels of trade costs as well as for an intermediate range of trade costs, the market equilibrium yields the socially optimal degree of agglomeration. An important implication of this result is that, on efficiency grounds, regional policy should foster the dispersion of firms for a range of high trade costs only, but agglomeration for a range of low trade costs. Hence, regional policies, such as those pursued by the European Union which are aimed at fostering dispersion in general, are counterproductive when trade integration is deep enough.
Keywords: R22; F22; F15; F12; R50; 330; economic geography; optimal agglomeration; welfare; regional policy; Regionalpolitik; Agglomerationseffekt; Transportkosten; Wirtschaftsintegration; Wohlfahrtseffekt; Neue ökonomische Geographie; Theorie; EU-Regionalpolitik; Kritik